Why are there discrepancies between depressed patients' Global Rating of Change and scores on the Patient Health Questionnaire depression module? A qualitative study of primary care in England. Issue 4 (4th May 2017) - Robinson, Jude; Khan, Naila; Fusco, Louise; Malpass, Alice; Lewis, Glyn; Dowrick, Christopher
Abstract : Objectives: Our aims were to investigate discrepancies between depressed patients' GlobalRating of Change (GRC) and scores on the Patient Health Questionnaire depression module (PHQ-9). Our objectives were to ascertain patients' views on the source and meaning of mismatches and assess their clinical significance. Design: Qualitative study nested within a cohort, in a programme investigating the indications for prescribing antidepressants that will lead to a clinical benefit. Setting: Primary care practices in north-west England. Participants: We invited 32 adults with a recent diagnosis of depression and evidence of mismatch between GRC and PHQ-9 Scores to participate. Of these, 29 completed our interviews; most were women, identified as white British, had high school education or higher, were employed or retired and had been depressed for a long time. Main measures: We conducted semistructured interviews with a topic guide, focusing on experiences of depression; treatment experiences and expectations; effectiveness of the questionnaires; reasons for the mismatch; and social factors. Interviews were transcribed and subjected to interpretative phenomenological analysis. Results: We identified four themes as explanations for mismatch between GRC and PHQ-9: perceptions that GRC provided a more accurate assessment of current mental state than PHQ-9; impact of recent negative or positive life events on either measure; personal understanding of depression as normally fluctuating, and tendency to underscore on PHQ-9 as a means of self-motivation; and lack of recall. Conclusions: The combined used of the PHQ-9 and a more open question better captures the patient's unique experiences of mental health. This approach ascertains the relevance of symptoms to the individual's experience and influences treatment decisions. Study registration: This study was an element of NIHR Programme Grant RP-PG 0610 10048.